Laminate and floor material
Patent Information
- Application Number
- JP2023130385
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-21
AI Technical Summary
【0009】 本発明の態様によれば、建物からの室内への臭気の透過を抑制することが可能な積層体及びその積層体を用いた床材を得ることができる。
Smart Images

Figure 2025025539000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate that is used by being laid on the floor surface of, for example, an indoor or outdoor building, and a flooring material including the laminate. [Background technology]
[0002] In the past, strong odors and unpleasant smells could occur indoors due to the deterioration of buildings and the living conditions of residents. Such odors are caused, for example, by various chemical substances contained in building materials laid on the floors of buildings or indoor odors that have permeated the building materials and spread throughout the room. In such cases, the livability and comfort of the house can decrease.
[0003] To address such issues, a flooring material has been proposed that is formed by providing a carbonized layer on the floor surface and that deodorizes the room by utilizing the surface activity of the carbonized material (Patent Document 1). Also, a laminate comprising an inorganic oxide layer and a protective layer on a resin substrate has been proposed, which suppresses adhesion of odors to buildings and diffusion of odors from buildings, and a flooring material (Patent Document 2). On the other hand, in recent years, there has been a growing trend to move away from plastic due to growing environmental awareness sparked by the problem of marine plastic waste, etc. From the perspective of reducing the amount of plastic materials used, the use of paper instead of plastic materials is being considered in various fields. For example, Patent Document 3 listed below discloses a gas barrier laminate in which a barrier layer is laminated on paper, and proposes a paper barrier material in which an anchor coat layer, a vapor deposition layer, and an overcoat layer are provided in this order on a paper base material. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-159941 A [Patent Document 2] JP 2020-131593 A [Patent Document 3] JP 2022-16714 A Summary of the Invention [Problem to be solved by the invention]
[0005] Odors that adhere to general flooring materials with high design properties can be difficult to remove by general cleaning or repair. However, when flooring materials with deodorizing properties according to the above-mentioned conventional techniques are used instead of general flooring materials, it is often difficult to impart a wide variety of design properties to the flooring materials. Regarding the use of plastic materials, when they are combined with wood substrates, it is difficult to recycle them at the time of disposal, and therefore it is desirable for them to be made of a single material. Against this background, in recent years, with consideration for the environment, there has been progress in the development of gas barrier materials that use paper as a base material rather than using synthetic resin films, etc.; however, there is a problem that when such materials are handled, such as when wrinkles are smoothed out or when pressure bonding methods such as ironing are used, cracks are generated in the barrier layer, resulting in a decrease in gas barrier properties.
[0006] Patent Document 3 describes that "the anchor coat layer contains a first polyolefin having a polar group. Such an anchor coat layer has excellent flexibility and can suppress cracking of the vapor deposition layer after bending, and can improve adhesion between the anchor coat layer and the vapor deposition layer," indicating an attempt to suppress cracking of the vapor deposition layer after bending. However, Patent Document 3 does not consider the fact that when an inorganic oxide is deposited as a deposited film, the barrier properties are less stable than when a metal is deposited.
[0007] The present invention has been made to solve such problems, and an object of the present invention is to provide a laminate capable of suppressing the diffusion of odors from building materials on which odors have adhered, and a flooring material using the laminate. Another object of the present invention is to provide a flooring material using a gas barrier laminate that uses paper and an inorganic oxide, the laminate having a high paper component ratio and stable and excellent gas barrier properties. [Means for solving the problem]
[0008] In order to solve the above problems, one representative laminate of the present disclosure is a laminate comprising, in this order, a paper base material, an anchor coat layer, a silica vapor deposition layer, and an overcoat layer, wherein the anchor coat layer and the overcoat layer are in direct contact with the silica vapor deposition layer, and the softening point of the anchor coat layer measured by local thermal analysis in a cross section in the thickness direction of the laminate is 180°C or higher. In order to solve the above problems, a flooring material according to another aspect of the present invention is characterized by comprising the above-mentioned laminate and a surface substrate attached to the surface of the laminate. Effect of the Invention
[0009] According to the aspects of the present invention, it is possible to obtain a laminate capable of suppressing the transmission of odors from a building to a room, and a flooring material using the laminate. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic cross-sectional view showing one configuration example of a laminate according to a first embodiment of the present invention. [Diagram 2] FIG. 4 is a schematic cross-sectional view showing one configuration example of a flooring material according to a second embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described below through embodiments, but the following embodiments do not limit the invention according to the claims. In addition, not all of the combinations of features described in the embodiments are necessarily essential to the solution of the invention. In addition, the drawings are schematic diagrams of the invention according to the claims, and the dimensions of the width, thickness, etc. of each part are different from the actual ones, and the ratios between them are also different from the actual ones. Hereinafter, each aspect of an embodiment of the present invention will be described with reference to the drawings.
[0012] Hereinafter, the laminate according to the embodiment of the present invention and a flooring material having the laminate will be described with reference to Figures 1 and 2. The laminate according to the embodiment of the present invention is laid, for example, under a floor board (surface base material such as decorative board) to be laid on the floor surface of a building. In the following description, the side of the laminate facing the floor board may be referred to as the "top" of the laminate, and the side of the laminate not facing the floor board (the floor side of the building) may be referred to as the "bottom".
[0013] 1. First embodiment 1 is a schematic cross-sectional view for explaining one configuration example of a laminate 100 according to a first embodiment of the present invention. The laminate 100 according to this embodiment is, for example, an odor-preventing sheet for building materials to be laid on the lower layer of a floor board to be laid on the floor surface of a building. As shown in Fig. 1, the laminate 100 includes a barrier layer 10, a paper substrate 11 provided on the side of an anchor coat layer 12 included in the barrier layer 10, and an adhesive layer 30 provided on the side of an overcoat layer 14 included in the barrier layer 10 or on the side of the paper substrate 11. More specifically, as shown in Fig. 1(a), the laminate 100 includes a barrier layer 10, a paper substrate 11 provided on the side of an anchor coat layer 12 included in the barrier layer 10, and an adhesive layer 30 provided on the side of an overcoat layer 14 included in the barrier layer 10. Also, as shown in Fig. 1(b), the laminate 100 includes a barrier layer 10, a paper substrate 11 provided on the side of an anchor coat layer 12 included in the barrier layer 10, and an adhesive layer 30 provided on the side of the paper substrate 11 opposite to the barrier layer 10 side. In the embodiment shown in FIG. 1( a ), a primer layer (not shown) may be provided between the overcoat layer 14 included in the barrier layer 10 and the adhesive layer 30 .
[0014] The barrier layer 10 is a layer that has the function of preventing indoor odors and odor-causing liquids from penetrating into the concrete or boards (hereinafter sometimes referred to as the "base") that make up the floor surface of the building, and of preventing various chemical substances from diffusing from the base into the room. The adhesive layer 30 is a layer provided for adhering the laminate 100 to a base. The laminate 100 may be arranged so that the barrier layer 10 faces a floor plate (not shown) or faces the floor surface of a building. In other words, the laminate 100 may be laid so that the adhesive layer 30 faces the floor surface of a building, and fixed to the floor surface of the building. Furthermore, when the barrier layer 10 side is provided facing the floor surface of a building, a primer layer (not shown) can be provided between the barrier layer 10 and the adhesive layer 30 to improve adhesion. The basic configuration of the laminate 100, that is, the configurations of the barrier layer 10, the paper base material 11, and the adhesive layer 30 will be described in detail below.
[0015] (1.1) Basic structure of laminate 100 The laminate 100 includes a barrier layer 10, a paper substrate 11, and an adhesive layer 30, as described above. The barrier layer 10 has a laminated structure including an anchor coat layer 12, a silica deposition layer 13, and an overcoat layer 14 in this order.
[0016] <Laminate> 1 is a schematic cross-sectional view showing the configuration of a gas barrier laminate according to a first embodiment of the present invention. The laminate 100 according to the first embodiment of the present invention comprises, in this order, a paper substrate 11, an anchor coat layer 12, a vapor deposition layer (silica vapor deposition layer) 13, and an overcoat layer 14. The anchor coat layer 12 contains at least one resin selected from the group consisting of, for example, acrylic resin, epoxy resin, acrylic urethane resin, polyester polyurethane resin, and polyether polyurethane resin. By using the laminate 100, it is possible to provide a flooring material that addresses the problem of eliminating plastic and marine littering, has a high ratio of paper components, and has stable and excellent water vapor barrier properties.
[0017] <Paper base material 11> The paper base material 11 is not particularly limited, and may be appropriately selected depending on the application of the laminate 100 to which it is applied. Specific examples of the paper substrate 11 include tissue paper, fine paper, art paper, cast coated paper, kraft paper, titanium paper, linter paper, paperboard, gypsum board paper, fine paper, coated paper, sulfate paper, glassine paper, parchment paper, paraffin paper, and Japanese paper. The basis weight of the paper base material 11 is not particularly limited, but the basis weight of the paper base material 11 is preferably 20 g / m 2 In the following cases, the paper base material 11 is too soft and wrinkles are likely to occur during processing. 2 In the above cases, the stiffness of the paper may make it difficult to handle during processing and may increase manufacturing costs. Taking these factors into consideration, the basis weight of the paper base material 11 is set to 20 g / m 2 More than 300g / m 2 The following range is preferable: 20 g / m 2 More than 200g / m 2 The following range is more preferable: 20 g / m 2 More than 100g / m 2 The following ranges are more preferred: Furthermore, the paper base material 11 may be subjected to surface treatment such as corona treatment, plasma treatment, or flame treatment, if necessary.
[0018] The paper base material 11 may have a coating layer (not shown) on the side in contact with the anchor coat layer 12 described below. The coating layer can prevent the resin constituting the anchor coat layer 12 from seeping into the paper base material 11, and can also serve as a sealant to fill in the unevenness of the paper base material 11. Therefore, if the paper base material 11 has a coating layer on its surface, the anchor coat layer 12 can be formed uniformly without defects such as uneven coating. The coating layer may contain, as a binder resin, for example, various copolymers such as styrene-butadiene, styrene-acrylic, and ethylene-vinyl acetate copolymers, polyvinyl alcohol resins, cellulose resins, paraffin (wax), and the like, and may also contain, as a filler, for example, clay, kaolin, calcium carbonate, talc, mica, and the like. The thickness of the coating layer (eg, clay coating layer) is not particularly limited, but is preferably within the range of 1 μm to 10 μm, and more preferably within the range of 3 μm to 8 μm.
[0019] The mass of the paper base material 11, more specifically the mass of the paper components contained in the paper base material 11, is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, based on the mass of the entire laminate 100. If the mass of the paper base material 11 is 50% by mass or more based on the mass of the entire laminate 100, the amount of plastic material used can be sufficiently reduced, the entire laminate 100 can be made of paper (can be labeled as "made of paper"), and it has excellent recyclability.
[0020] <Barrier layer 10> [Anchor coat layer] The anchor coat layer 12 is provided on the surface of the paper substrate 11 and may contain at least one type of polar group or may contain polyolefin. The anchor coat layer 12 may also contain a polyvinyl alcohol-based resin. The total content of resins having polar groups (e.g., polyolefins having polar groups) in the anchor coat layer 12 is, for example, 50 mass% or more, more preferably 70 mass% or more, even more preferably 90 mass% or more, and most preferably 100 mass%, relative to the total mass of the anchor coat layer 12.
[0021] The polyolefin having a polar group may have at least one selected from a carboxyl group, a salt of a carboxyl group, a carboxylic anhydride group, and a carboxylic acid ester. For example, ethylene or propylene may be copolymerized with an unsaturated carboxylic acid (an unsaturated compound having a carboxyl group such as acrylic acid, methacrylic acid, or maleic anhydride), an unsaturated carboxylic acid ester, or a salt obtained by neutralizing a carboxylic acid with a basic compound, or may be copolymerized with vinyl acetate, an epoxy compound, a chlorine compound, a urethane compound, a polyamide compound, or the like. Specific examples include copolymers of acrylic acid ester and maleic anhydride, ethylene-vinyl oxide copolymers, and ethylene-glycidyl methacrylate copolymers.
[0022] The polyvinyl alcohol resin is, for example, a fully saponified polyvinyl alcohol resin, a partially saponified polyvinyl alcohol resin, a modified polyvinyl alcohol resin, or an ethylene-vinyl alcohol copolymer resin. The degree of polymerization of the polyvinyl alcohol resin is preferably 300 or more and 1700 or less. If the degree of polymerization is 300 or more, the gas barrier property and bending resistance of the laminate 100 become good, and if the degree of polymerization is 1700 or less, the viscosity of the coating liquid of the polyvinyl alcohol resin described below becomes low, and the coating property becomes good.
[0023] The anchor coat layer 12 may contain other components in addition to the above-mentioned polyolefin having a polar group and polyvinyl alcohol resin. Examples of the other components include resins such as polyolefins other than the above-mentioned polyolefin having a polar group, polyacrylic, polyester, polyurethane, polycarbonate, polyurea, melamine, phenol, polyethyleneimine, polylactic acid, polyamide, polyimide, starch and its derivatives, and cellulose derivatives, as well as additives such as silane coupling agents, organic titanates, glycerin, glycols, casein, and wax.
[0024] The anchor coat layer 12 is provided to improve adhesion to the paper base material 11 and to improve the gas barrier properties of the laminate 100. Because the anchor coat layer 12 contains at least one type of polar group, the laminate 100 has excellent gas barrier properties, and because it contains a polyvinyl alcohol-based resin, it has excellent water vapor barrier properties and oxygen barrier properties, and because it contains polyolefin, it is possible to form a dense film due to the crystallinity of the polyolefin, and water vapor barrier properties are expressed.
[0025] The lower limit of the thickness of the anchor coat layer 12 is, for example, 1 μm or more, more preferably 2 μm or more. The upper limit may be 20 μm or less, more preferably 10 μm or less, and even more preferably 5 μm or less. If the thickness of the anchor coat layer 12 is 1 μm or more, the deposition layer 13 can be laminated evenly. The thicker the anchor coat layer 12 is, the more efficiently the unevenness of the paper base material 11 can be filled, and the deposition layer 13 can be laminated even more evenly. If the thickness of the anchor coat layer 12 is 20 μm or less, the above layers can be laminated evenly while suppressing costs.
[0026] The softening temperature of the anchor coat layer 12 measured by local thermal analysis is 180° C. or higher, more preferably 185° C. or higher, and even more preferably 190° C. or higher. There is no particular upper limit to the softening temperature. If the softening temperature of the anchor coat layer 12 is 180° C. or higher, it is possible to suppress a decrease in the density of the deposition layer 13. The higher the softening temperature, the more the anchor coat layer 12 softens and expands due to the heat of the deposition material such as SiOx particles during deposition, so that it is possible to further suppress the occurrence of macrocracks in the deposition layer (silica deposition layer) 13 and the decrease in density of the deposition layer 13. The softening temperature of the anchor coat layer 12 can be adjusted by adjusting the constituent materials of the anchor coat layer 12 or the ratio of the resins to be combined.
[0027] The method of providing the anchor coat layer 12 includes, for example, a method of applying a coating liquid containing the constituent materials and solvent of the anchor coat layer 12 on the paper substrate 11 and drying it. Examples of the solvent contained in the coating liquid for forming the anchor coat layer 12 include water, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-pentyl alcohol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate. These solvents may be used alone or in combination of two or more. Among these, from the viewpoint of characteristics, methyl alcohol, ethyl alcohol, isopropyl alcohol, toluene, ethyl acetate, methyl ethyl ketone, and water are preferred. Furthermore, from the viewpoint of environment, methyl alcohol, ethyl alcohol, isopropyl alcohol, and water are preferred.
[0028] [Vapour-deposited layer] The deposition layer 13 is a layer formed by depositing silica, which is an inorganic compound, and may contain silicon oxide (SiOx) or the like. The thickness of the deposition layer 13 may be appropriately set depending on the intended use, but the lower limit is preferably 10 nm or more, more preferably 20 nm or more, and even more preferably 30 nm or more. The upper limit of the thickness of the deposition layer 13 is preferably 100 nm or less, and more preferably 80 nm or less. By setting the thickness of the deposition layer 13 to 10 nm or more, it is easy to ensure sufficient continuity of the deposition layer 13, and by setting the thickness to 100 nm or less, it is possible to sufficiently suppress curling in the laminate and cracking in the deposition layer, and it is easy to achieve sufficient gas barrier performance and flexibility.
[0029] The deposition layer 13 is preferably formed by a vacuum deposition means from the viewpoint of water vapor and oxygen gas barrier performance and film uniformity. There are known deposition means such as vacuum deposition, sputtering, and chemical vapor deposition (CVD), but vacuum deposition is preferred because of its fast deposition rate and high productivity. Among the vacuum deposition methods, deposition means using electron beam heating is particularly effective because the deposition rate can be easily controlled by the irradiation area and electron beam current, and the temperature of the deposition material can be raised and lowered in a short time.
[0030] [Overcoat layer] The overcoat layer 14 is provided on the surface of the vapor-deposited layer 13 so as to be in contact with the vapor-deposited layer 13. The overcoat layer 14 may contain, for example, a polyolefin having a polar group. The polyolefin having a polar group may have, for example, at least one selected from a carboxyl group, a salt of a carboxyl group, a carboxylic anhydride group, and a carboxylic ester. Specifically, a copolymer of an acrylic acid ester and maleic anhydride, an ethylene-vinyl acetate copolymer, an ethylene-glycidyl methacrylate copolymer, or the like may be used.
[0031] By including a polyolefin having a polar group, the overcoat layer 14 has excellent flexibility, can suppress cracking of the deposition layer 13 after bending, and has excellent adhesion to the deposition layer 13. Furthermore, by including the overcoat layer 14 in the above-mentioned polyolefin having a polar group, it is possible to obtain a laminate 100 having excellent water vapor barrier properties. The content of the polyolefin having a polar group in the overcoat layer 14 is, for example, 50% by mass or more, more preferably 70% by mass or more, even more preferably 90% by mass or more, and most preferably 100% by mass.
[0032] The overcoat layer 14 may contain other components in addition to the polyolefin having a polar group, such as a silane coupling agent, an organic titanate, polyacrylic, polyester, polyurethane, polycarbonate, polyurea, polyamide, a polyolefin emulsion, polyimide, melamine, and phenol. The lower limit of the thickness of the overcoat layer 14 is, for example, 2 μm or more, and more preferably 3 μm or more. The upper limit of the thickness of the overcoat layer 14 is, for example, 10 μm or less, more preferably 8 μm or less, and even more preferably 5 μm or less. If the thickness of the overcoat layer 14 is 10 μm or less, the adhesion to the deposition layer 13 and the barrier properties can be sufficiently exhibited while suppressing costs.
[0033] The method of providing the overcoat layer 14 includes, for example, a method of applying a coating liquid containing the above-mentioned polyolefin and a solvent onto the deposition layer 13 and drying it. Examples of the solvent contained in the coating liquid for forming the overcoat layer 14 include water, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-pentyl alcohol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate. These solvents may be used alone or in combination of two or more. Among these, from the viewpoint of characteristics, methyl alcohol, ethyl alcohol, isopropyl alcohol, toluene, ethyl acetate, methyl ethyl ketone, and water are preferred. Furthermore, from the viewpoint of environment, methyl alcohol, ethyl alcohol, isopropyl alcohol, and water are preferred. The polyolefins having polar groups contained in the anchor coat layer 12 and the overcoat layer 14 may be the same or different, but considering ease of production, etc., it is preferable that they are the same.
[0034] <Adhesive layer> The adhesive layer 30 may be composed of only the adhesive layer 32 (i.e., it does not need to have the adhesive base material 31), or it may be composed of the adhesive base material 31 and the adhesive layer 32 provided on the adhesive base material 31. The adhesive base material 31 is preferably a support made of a mesh sheet material, etc. The support may be, for example, a nonwoven fabric or a woven fabric. The adhesive base material 31 may be a laminate cloth in which the above-mentioned support is bonded with, for example, a resin film, or a coating cloth in which the surface of a support is covered with a resin material.
[0035] The adhesive layer 32 may take various forms. For example, the adhesive layer 32 may be a separate layer formed by laminating a resin on the surface of the paper substrate 11 or the surface of the overcoat layer 14, or may be a separate layer formed by laminating a resin on the surface of a primer layer (not shown) provided on the surface of the overcoat layer 14. Alternatively, the adhesive layer 32 may be an adhesive sheet formed by impregnating the adhesive substrate 31 with a resin (i.e., an adhesive layer in a form in which the adhesive substrate 31 is embedded in a resin). Furthermore, the adhesive layer 32 may be a layer formed by laminating a resin on the surface of the adhesive substrate 31. Among these forms, the adhesive layer 32 is preferably an adhesive sheet formed by impregnating the adhesive substrate 31 with a resin described later. The adhesive layer 32 can be formed from a conventionally known resin material.
[0036] Examples of resin materials constituting the adhesive layer 32 include styrene resins such as polystyrene and polyα-methylstyrene, acrylic resins such as polymethyl methacrylate and polyethyl acrylate, vinyl resins such as polyvinyl chloride, polyvinyl acetate, vinyl chloride-vinyl acetate copolymer, polyvinyl butyral, and polyvinyl acetal, polyester resins, polyamide resins, epoxy resins, polyurethane resins, petroleum resins, synthetic resins such as ionomers, ethylene-acrylic acid copolymers, and ethylene-acrylic acid ester copolymers, cellulose derivatives such as nitrocellulose, ethylcellulose, cellulose acetate propionate, and cellulose acetate butyrate, rosin, rosin-modified maleic acid resins, ester gum, polyisobutylene rubber, butyl rubber, styrene-butadiene rubber, butadiene-acrylonitrile rubber, and polychlorinated olefins. These resins may be used alone or in combination of two or more.
[0037] The amount of adhesive layer 32 formed (the amount of solids remaining after the coating liquid is applied and dried) depends on the material of the base to be bonded and the required performance, but is preferably 0.1 g / m 2 More than 50.0g / m 2 Preferably, the content is 1.0 g / m or less. 2 More than 50.0g / m 2 More preferably, it is 5.0 g / m or less. 2 More than 50.0g / m 2 More specifically, in the adhesive layer 32 formed by impregnating (embedding) the above-mentioned resin into the adhesive substrate 31, the amount of the resin (the amount of solid content remaining after the coating liquid is applied and dried) is 0.1 g / m or less. 2 More than 50.0g / m 2 Preferably, the content is 1.0 g / m or less. 2 More than 50.0g / m 2 More preferably, it is 5.0 g / m or less. 2 More than 6.0g / m 2 It is even more preferable that:
[0038] In addition, known additives other than resins can be used in the adhesive layer 32 within the scope that does not impair the above-mentioned performance. Examples of additives that can be used include inorganic pigment fine particles, isocyanate compounds, silane coupling agents, dispersants, viscosity modifiers, release agents, slipping agents such as wax-resin fillers, ultraviolet absorbers, light stabilizers, antioxidants, fluorescent brightening agents, and antistatic agents. By providing the adhesive layer 30, the laminate 100 becomes a so-called tucked odor-preventing sheet for building materials. Therefore, when the laminate 100 is applied, it can be easily attached to a base, and the application property of the laminate 100 can be improved.
[0039] (1.2) Effects of the First Embodiment The laminate 100 as described above has the following effects. (1) The laminate 100 has a silica vapor deposition layer 13, which can prevent odors from adhering to a building or can transmit odors and prevent the odors from diffusing into a room. Therefore, the laminate 100 can exhibit a high deodorizing function. (2) It is preferable that the thickness of the anchor coat layer 12 of the laminate 100 is in the range of 1 μm to 20 μm. With this configuration, the laminate 100 can efficiently fill in the irregularities on the surface of the paper base material 11, and the deposition layer 13 can be laminated uniformly. (3) In the laminate 100, if the softening temperature of the anchor coat layer 12 is 180° C. or higher, a decrease in the density of the vapor deposition layer 13 can be suppressed. (4) It is preferable that the thickness of the vapor deposition layer 13 is 10 nm or more and 100 nm or less in the laminate 100. With this configuration, the laminate 100 can obtain sufficient gas barrier performance and flexibility while suppressing the occurrence of curling and cracking. (5) It is preferable that the thickness of the overcoat layer 14 is 2 μm or more and 10 μm or less in the laminate 100. With this configuration, the laminate 100 can have improved gas barrier properties while keeping production costs down. (6) The laminate 100 becomes a so-called tucked deodorizing sheet for building materials by providing the adhesive layer 30. Therefore, the laminate 100 can be easily applied and has high application properties.
[0040] 2. Second embodiment Next, a configuration example of a flooring material having an odor-preventing sheet, which is the laminate 100, according to a second embodiment will be described with reference to Fig. 2. Fig. 2 is a schematic cross-sectional view showing the configuration of a flooring material 200 having the laminate 100. As shown in FIG. 2, the flooring material 200 includes a laminate 100 and a surface substrate 210 laminated on the surface of the laminate 100 (i.e., on the barrier layer 10 or on the paper substrate 11). More specifically, as shown in FIG. 2(a), the flooring material 200 includes a barrier layer 10, a paper substrate 11 provided on the side of the anchor coat layer 12 included in the barrier layer 10, an adhesive layer 30 provided on the side of the overcoat layer 14 included in the barrier layer 10, and a surface substrate 210 provided on the side of the paper substrate 11 opposite the barrier layer 10. Also, as shown in FIG. 2(b), the flooring material 200 includes a barrier layer 10, a paper substrate 11 provided on the side of the anchor coat layer 12 included in the barrier layer 10, an adhesive layer 30 provided on the side of the paper substrate 11 opposite the barrier layer 10, and a surface substrate 210 provided on the side of the barrier layer 10 opposite the paper substrate 11. The laminate 100 according to this embodiment has a similar configuration to the laminate 100 according to the first embodiment described above, and therefore a description thereof will be omitted here.
[0041] The surface substrate 210 may be, for example, a decorative material in which a decorative sheet is laminated on the surface of a substrate, or may be a floor board or a tatami mat. The laminate 100 and the surface substrate 210 are preferably attached to each other. In this embodiment, the adhesive used to bond the laminate 100 and the surface base material 210 is not limited to, and any type can be used, such as, for example, a water-based adhesive, a solvent-based adhesive, a chemical reaction adhesive, a hot melt adhesive, etc. As the adhesive, a publicly known adhesive or a commercially available product can be appropriately selected and used. Furthermore, in the embodiment shown in FIG. 2( b ), when the barrier layer 10 and the surface substrate 210 are bonded together, a primer layer (not shown) may be provided between the barrier layer 10 and the surface substrate 210 .
[0042] (2.1) Flooring composition <Surface base material> The following describes the case where the surface base material 210 is a decorative material 210a. As shown in Fig. 2, the decorative material 210a is provided on the surface of the laminate 100 facing the barrier layer 10 or on the surface facing the paper base material 11. Fig. 2(a) shows a form in which the decorative material 210a is provided on the surface of the paper base material 11, and Fig. 2(b) shows a form in which the decorative material 210a is provided on the surface of the barrier layer 10. Decorative material 210a has at least decorative base material 220 which is the base material of decorative material 210a, and decorative sheet 230 laminated on the upper surface of decorative base material 220. Decorative sheet 230 is, for example, a sheet member having a pattern or being colored.
[0043] [Cosmetic base material] The decorative base material 220 is a base material made of various materials such as wood, metal, synthetic resin, etc., and any material similar to the base material (layer) in conventional flooring materials can be used. An example of the decorative base material 220 made of a wood-based material is laminated wood. Moreover, an example of the decorative base material 220 made of a metallic material is an aluminum plate. In addition, examples of the decorative base material 220 made of a synthetic resin-based material include resin sheets formed of thermoplastic resins including polyolefin-based resins such as polyethylene and polypropylene, which have excellent so-called hinge properties such as deformability, crack resistance, and recovery properties.
[0044] [Decorative sheet] The decorative sheet 230 is, for example, a sheet in which a picture pattern layer is printed on the front side of a polyolefin resin sheet, and a transparent resin layer and a surface protection layer are laminated in this order on the front side of the picture pattern layer. The polyolefin resin sheet is a sheet body made of a polyolefin resin and formed by a calendar method, an inflation method, a T-die extrusion method or the like. Examples of polyolefin resins include polypropylene (PP), polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), and polybutylene naphthalate (PBN).
[0045] The picture pattern layer is a layer that imparts design to the decorative sheet 230 with a desired pattern. The type of pattern is not particularly limited, and examples include wood grain, stone grain, sand grain, tiled pattern, brickwork pattern, fabric pattern, leather-stained pattern, geometric figures, letters, symbols, and abstract patterns. The picture pattern layer may be a single-color decorative sheet 230 without a pattern. A known decorative sheet may be used as the decorative sheet 230. The flooring material 200 according to this embodiment may have a buffer layer (not shown) provided on the surface of the decorative base material 220 opposite the decorative sheet 230, for example. As described above, the flooring material 200 having the laminate 100 and the surface substrate 210 is preferable because it allows the laminate 100 to be laid simultaneously with the laying of the flooring material 200.
[0046] (2.2) Effects of the Second Embodiment The flooring material 200 as described above has the following effects in addition to the effects of the first embodiment. (7) The flooring material 200 having the laminate 100 can be laid simultaneously with the laying of the flooring material 200. This makes it possible to lay the laminate 100 without increasing the number of work steps.
[0047] [Example] The laminate according to this embodiment will be described below with reference to examples. In the examples, odors were evaluated in a room where a floor covering was laid using the laminate according to this embodiment, and in a room where a floor covering was laid without using the laminate according to this embodiment.
[0048] <Preparation of Laminate> Example 1 Paper (clay coated paper, paper weight: 50g / m 2 A solution of polyepoxy resin was applied onto the clay coat surface (clay coat layer thickness: 5 μm) using a bar coater and dried in an oven to form an anchor coat layer with a thickness of 3 μm. The solution was prepared by mixing 24 parts by mass of Maxive C93AT (manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 2 parts by mass of Maxive M-100 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) with 17 parts by mass of a 1:1 (mass ratio) mixed solvent of methanol and ethyl acetate. Subsequently, SiOx was vapor-deposited onto the anchor coat layer to a thickness of 30 nm to form a silica vapor-deposited layer. An aqueous dispersion of polyolefin containing a carboxyl group salt was applied thereon using a bar coater and dried in an oven to form an overcoat layer having a thickness of 3 μm. In this way, a laminate (barrier layer with paper) according to Example 1 was obtained.
[0049] Example 2 A laminate according to Example 2 was obtained in the same manner as in Example 1, except that a urethane-cured acrylic resin, which is a cured product of an acrylic polyol and a polyisocyanate, was applied to a thickness of 1 μm as the anchor coat layer. Example 3 A laminate according to Example 3 was obtained in the same manner as in Example 1, except that a urethane-cured acrylic resin, which is a cured product of an acrylic polyol and a polyisocyanate, was applied to a thickness of 3 μm as the anchor coat layer. Example 4 A laminate according to Example 4 was obtained in the same manner as in Example 1, except that the thickness of the silica vapor deposition layer was 10 nm.
[0050] Example 5 A laminate according to Example 5 was obtained in the same manner as in Example 1, except that the thickness of the silica vapor deposition layer was 100 nm. Example 6 A laminate according to Example 6 was obtained in the same manner as in Example 1, except that the thickness of the overcoat layer was 2 μm. Example 7 A laminate according to Example 7 was obtained in the same manner as in Example 1, except that the thickness of the overcoat layer was 10 μm.
[0051] Comparative Example 1 A coating solution of polyvinyl alcohol resin with a saponification degree of 98% and a polymerization degree of 500 dissolved in a solvent of water / IPA = 8 / 2 (mass ratio) was applied onto the clay-coated surface of the paper using a bar coater and dried in an oven to obtain an anchor coat layer with a thickness of 3 μm. The silica deposition layer and the overcoat layer were formed in the same manner as in Example 1 to form a laminate (paper-attached barrier layer) according to Comparative Example 1.
[0052] Comparative Example 2 A laminate according to Comparative Example 2 was obtained in the same manner as in Comparative Example 1, except that the thickness of the anchor coat layer was 6 μm. Comparative Example 3 A laminate according to Comparative Example 3 was obtained in the same manner as in Comparative Example 1, except that the constituent resin of the anchor coat layer was a polyolefin containing a salt of a carboxyl group. Comparative Example 4 A laminate according to Comparative Example 4 was obtained in the same manner as in Comparative Example 1, except that the constituent resin of the anchor coat layer was a polyolefin containing a salt of a carboxyl group and the thickness was 6 μm.
[0053] An adhesive sheet (#703N, manufactured by Ebisu Kasei Co., Ltd.) was attached to the surface of the barrier layer of each laminate (paper-attached barrier layer) in Examples 1 to 7 and Comparative Examples 1 to 4. The adhesive layer was made by applying an acrylic resin to the surface of a laminate cloth, which was the adhesive substrate, and drying it to form an adhesive layer. In this manner, each of the laminates of Examples 1 to 7 and Comparative Examples 1 to 4 was formed.
[0054] <Local thermal analysis measurement> [Softening temperature measurement] The softening temperature of the resin layer (anchor coat layer) was measured by the method described below. The sample was cut into a rectangular shape with a base of 1.0 mm and a height of 5.0 mm using a razor, embedded in light-curing resin, and cured using a halogen lamp KTX-100R (D-800 manufactured by Toagosei Co., Ltd.). The photocured test piece was fixed in an insert for an AFM sample holder, and the cross section of the film was cut with a glass knife at room temperature (25°C).
[0055] After that, final cross-section cutting was performed at room temperature with a diamond knife at a cutting speed of 2.0 mm / s and a cutting film thickness of 200 nm, and cutting was completed when a mirror surface was obtained. An ultramicrotome (Leica EM UC7) and a cryosystem (Leica EM FC7) were used as cross-section cutting devices. The cutting direction of the knife was perpendicular to the film thickness direction of the layer. The cross-sectioned test piece was fixed with an insert for an AFM sample holder and used for softening temperature measurement. The atomic force microscope (AFM) was an MFP-3D-SA manufactured by Oxford Instruments, with a local thermal analysis option available as a Zterm system, and the cantilever was an AN2-200 manufactured by Anasys Instruments with a spring constant of 0.5 to 3.5 N / m. Softening temperature and shape measurements were performed.
[0056] The cantilever contact pressure (change in cantilever deflection (Deflectin)) was 2.0 V, the voltage application rate (heating rate) was 0.5 V / sec, and the maximum applied voltage was 7.1 V. After Detrend correction, the measurement surface, i.e., the cross section of the anchor coat layer, was heated, causing the measurement surface to expand and the height of the cantilever to increase. When the measurement surface was further heated, it softened and the height position of the cantilever dropped by 20 nm, at which point the measurement was terminated. If the height position did not drop 20 nm from the change point and reached the maximum applied voltage, the maximum applied voltage during Detrend correction and measurement was increased by 0.5 V and the measurement was repeated. The voltage applied was determined as the voltage at the point where the vertical height of the cantilever was at its maximum, and the voltage value was read.
[0057] Next, a constitutive curve was created to calculate the softening temperature of the anchor coat layer. The calibration samples used were polycaprolactone (melting point: 60°C), low-density polyethylene (LDPE, melting point: 112°C), polypropylene (PP, melting point: 166°C), and polyethylene terephthalate (PET, melting point: 250°C). The cantilever contact pressure (change in cantilever deflection) was 2.0 V, and the voltage application rate (heating rate) was 0.5 V / sec. The calibration sample was measured 10 times by changing the measurement position, and a calibration curve was created by approximating the average value of the applied voltage at the softening point and the melting point with a cubic function using the least squares method. In addition, the softening temperature error at this time is considered to be ±10°C. Using the configuration curve of applied voltage and melting point (melting peak temperature), the applied voltage at the softening point of the resin layer (anchor coat layer) was converted to temperature, which was taken as the softening temperature in this example. The results thus obtained are shown in Tables 1 to 3.
[0058] <Evaluation> The laminates obtained in the above-mentioned Examples 1 to 7 and Comparative Examples 1 to 4 were laid under floorboards (surface base material such as decorative boards) in different rooms, and the following evaluations were carried out for each room.
[0059] [Evaluation of odor suppression function] Indoor air quality was measured in each room on multiple measurement days to confirm the odor suppression effect. To evaluate the odor suppression function, the first three indoor air quality measurements were taken in each room on different measurement days. Each indoor air quality measurement was taken for about five hours. Indoor air quality measurements included volatile organic compounds (VOCs), aldehydes, ammonia, formic acid, and acetic acid. Each substance was analyzed using the following methods. Volatile organic compounds: Solid-phase collection-thermal desorption-gas chromatography-mass spectrometry (GC / MS) method Aldehydes: DNPH collection - solvent extraction - high performance liquid chromatography (HPLC) method Ammonia, formic acid, acetic acid: Liquid-phase collection - ion chromatography (IC) method Each of the above analyses was evaluated using the following four-point scale: "◎", "○", "△", and "×".
[0060] <Evaluation criteria> ◎: When the indoor concentration of each substance is below the Ministry of Health, Labor and Welfare indoor concentration guideline value and the concentration reduction effect of each substance is excellent. ○: When the indoor concentration of each substance is below the Ministry of Health, Labor and Welfare indoor concentration guideline value and the effect of reducing the concentration of each substance has been confirmed. △: When the indoor concentration of each substance is below the Ministry of Health, Labor and Welfare indoor concentration guideline value, or the effect of reducing the concentration of each substance has been confirmed. ×: When the indoor concentration of each substance exceeds the indoor concentration guideline value set by the Ministry of Health, Labor and Welfare, and the effect of reducing the concentration of each substance cannot be confirmed. In this embodiment, an evaluation of "A" was deemed to be acceptable.
[0061] (Evaluation Results) The evaluation results of the odor suppression function are shown in Tables 1 to 3 below.
[0062] [Table 1]
[0063] [Table 2]
[0064] [Table 3]
[0065] As shown in Tables 1 to 3, in the rooms where the laminates of Examples 1 to 7 were used, the concentrations of volatile organic compounds, aldehydes, ammonia, formic acid, and acetic acid were below the Ministry of Health, Labor, and Welfare indoor concentration guideline values, or the effect of reducing the concentration of each substance was confirmed to be significant. On the other hand, in the rooms where the laminates of Comparative Examples 1 to 4 were used, it was not possible to confirm that the concentrations of each substance were below the Ministry of Health, Labor, and Welfare indoor concentration guideline values, or that the effect of reducing the concentration of each substance was present. From the above evaluation results, it was confirmed that it is possible to suppress the diffusion of odors by laying the laminate of this embodiment under a floor board (surface base material such as decorative board).
[0066] Furthermore, for example, the present invention can have the following configuration. (1) A laminate comprising a paper substrate, an anchor coat layer, a silica deposition layer, and an overcoat layer in this order, the anchor coat layer and the overcoat layer are in direct contact with the silica deposition layer; A laminate, characterized in that the softening temperature of the anchor coat layer measured by local thermal analysis in a cross section in the thickness direction of the laminate is 180°C or higher. (2) A laminate comprising a paper substrate, an anchor coat layer, a silica deposition layer, and an overcoat layer in this order, The laminate, wherein the anchor coat layer contains at least one of an epoxy resin, an acrylic urethane resin, an acrylic resin, a polyester polyurethane resin, and a polyether polyurethane resin. (3) The laminate according to the above (1) or (2), wherein the overcoat layer contains at least one type of polyolefin having a polar group. (4) The laminate according to any one of (1) to (3) above, wherein the thickness of the silica vapor deposition layer is within the range of 10 nm to 100 nm. (5) The laminate according to any one of the above (1) to (4), wherein the overcoat layer has a thickness in the range of 2 μm to 10 μm. (6) The laminate according to any one of (1) to (5) above, characterized in that the mass of the paper component contained in the paper base material is 50 mass% or more based on the mass of the entire laminate. (7) The laminate according to any one of (1) to (6) above, further comprising an adhesive layer on either the exposed surface side of the paper base material or the exposed surface side of the overcoat layer. (8) The adhesive layer includes an adhesive base material and a pressure-sensitive adhesive layer, The adhesive substrate is a mesh sheet material, The laminate according to (7) above, wherein the adhesive layer is a layer containing an acrylic resin that embeds the mesh sheet material. (9) A flooring material comprising the laminate according to any one of (1) to (8) above, and a surface substrate laminated on a surface of the laminate.
[0067] The scope of the present invention is not limited to the exemplary embodiments shown and described, but includes all embodiments that achieve equivalent effects to the object of the present invention. Moreover, the scope of the present invention is not limited to the combination of inventive features defined by the claims, but may be defined by any desired combination of specific features among all the respective disclosed features. [Explanation of symbols]
[0068] 10: Barrier layer 11:Paper base material 12: Anchor coat layer 13: Silica deposition layer (deposition layer) 14: Overcoat layer 30: Adhesive layer 31: Adhesive base material 32:Adhesive layer 100: Laminate 200:Flooring 220: Decorative substrate 230: Decorative sheet
Claims
1. A laminate comprising a paper substrate, an anchor coat layer, a silica deposition layer, and an overcoat layer in this order, the anchor coat layer and the overcoat layer are in direct contact with the silica deposition layer; A laminate, characterized in that the softening temperature of the anchor coat layer measured by local thermal analysis in a cross section in the thickness direction of the laminate is 180°C or higher.
2. A laminate comprising a paper substrate, an anchor coat layer, a silica deposition layer, and an overcoat layer in this order, The laminate, wherein the anchor coat layer contains at least one of an epoxy resin, an acrylic urethane resin, an acrylic resin, a polyester polyurethane resin, and a polyether polyurethane resin.
3. 3. The laminate according to claim 1, wherein the overcoat layer comprises at least one polyolefin having a polar group.
4. 3. The laminate according to claim 1, wherein the thickness of the silica vapor deposition layer is in the range of 10 nm to 100 nm.
5. 3. The laminate according to claim 1, wherein the overcoat layer has a thickness in the range of 2 [mu]m to 10 [mu]m.
6. 3. The laminate according to claim 1, wherein the mass of the paper component contained in the paper base material is 50 mass % or more based on the mass of the entire laminate.
7. 3. The laminate according to claim 1, further comprising an adhesive layer on either the exposed surface side of the paper base material or the exposed surface side of the overcoat layer.
8. The adhesive layer includes an adhesive base material and a pressure-sensitive adhesive layer, The adhesive substrate is a mesh sheet material, 8. The laminate according to claim 7, wherein the adhesive layer is a layer containing an acrylic resin that embeds the mesh sheet material.
9. A flooring material comprising the laminate according to claim 8 and a surface substrate laminated on a surface of the laminate.
Citation Information
Patent Citations
Floor material
JP2013159941A
Laminate and floor material
JP2020131593A
Gas barrier laminate and packaging bag
JP2022016714A